Peran Perempuan Dalam Ketersediaan Pangan Rumahtangga (Studi Kasus Pada Masyarakat Petani Padi Di Gampong Blang Pala, Kecamatan Banda Baro, Kabupaten Aceh Utara, Provinsi Aceh) - Shamadiyah, Nurasih; Nasution, Pangeran Putra Perkasa Alam (LPPM Universitas Malikussaleh - Indonesia, 2018)
The rice farmers community as producers of staple food for food needs of the community is considered to have certainty in food security. Not only they have to produce food commodities, but they are also responsible for the availability of food for all their families and the community. This study aims to describe the division of roles between women and men in agricultural and non-farm activities (on farm and off farm) in order to fill household food security in rice farming communities in Blang Pala Village, Banda Baro District, Aceh Utara Regency, Aceh Province. The study was conducted by in-depth interviews with ethno-science as the approach. The informants are determined based on several conditions, such as full of involvement in agricultural and non-agricultural activities, informants who are directly involved in the cultural atmosphere, and have different social and cultural backgrounds with researchers. Informants in this study were divided into female farmers and male farmers. The results of the study show that women have a real and very important contribution to food security of their family. Women have a very important role in the effort to provide food at the household level because women are fully involved both in agricultural activities and outside agricultural activities. Although basically those who make a livelihood are not the main task of women, but when it comes to providing food, it becomes a duty of women in their families